Impact evaluation of Community-Led Total Sanitation (CLTS) in rural Mali: Final report - Maria Laura Alzua; Amy Janel Pickering; Habiba Djebbari; Carolina Lopez; Juan Camilo Cardenas; Maria Adelaida Lopera; Nicolas Osbert; Massa Coulibaly (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
Community-Led Total Sanitation (CLTS) has been adopted in Mali to scale-up sanitation in rural areas and accelerate progress towards the MDG target on sustainable access to basic sanitation. However, few impact evaluations of community-based sanitation interventions have been conducted so far. This study presents the results of a randomized controlled trial for studying the effect of CLTS in rural Mali. 121 communities were randomly selected out of a sample of 402 villages identified as fit for the CLTS intervention based on high rates of open defecation and an expressed interest to improve the situation. Half of the 121 selected communities were randomly assigned to receive CLTS while the other half would be control villages. Baseline information was collected in all the communities prior to the intervention (March to April 2011). The data collected covered household demographic characteristics, health information, anthropometrics, and sanitation and water quality samples. Follow up information was collected between April and June 2013, 6 to 19 months after the intervention finished (depending on the villages). The study found a very significant increase in access to private latrines (which almost doubled among households in CLTS villages); improved quality of latrines and reduction in open defecation practices (self-reported open defecation rates fell by 70% among adults and by 50% among children under-five). CLTS households were three times more likely to have soap present and five times more likely to have water present at the hand washing facility. But no improvement of water quality was found.
Keywords: 330